The Effect of Controlled Release Fertilizer On The Growth of Oil Palm (Elaeis Guineensis Jacq.) Seedlings In The Pre-Nursery - Bela Ayu Pratiwi; Adi Noor Prayogi; Bambang Utoyo; AH. Maftuh Hafidh Zuhdi; Husna (Agricultural Science, 2026)
Improving oil palm production can be achieved through better cultivation management, including proper nursery practices. The quality of seedlings at the early growth stage plays a crucial role in determining field performance, making efficient fertilization essential from the pre-nursery phase. One of the fertilization technologies developed to improve nutrient uptake efficiency is the application of Controlled Release Fertilizer (CRF). This study aimed to evaluate the effect of CRF compared with conventional NPK fertilizer on the growth of oil palm seedlings. The experiment was conducted for three months using a Completely Randomized Design (CRD) with four treatments: no fertilizer (P0), NPK (P1), NPK + CRF (P2), and CRF (P3). Data were analyzed using ANOVA at a 5% significance level, followed by the LSD test when significant differences were detected. The results showed that treatments P2, P3, and P4 produced better growth responses than the control in all observed parameters, including plant height, number of leaves, leaf greenness, stem diameter, and leaf area. Fertilizer application significantly improved seedling growth, while CRF, either applied alone or in combination with NPK, produced growth responses comparable to conventional fertilization. These findings indicate that CRF has the potential to be used as an effective fertilization alternative to support oil palm seedling growth in the pre-nursery.